Detection of sentinel lymph node using contrast-enhanced agent, Sonazoid™, and evaluation of its metastasis with superb microvascular imaging in oral and oropharyngeal cancers: a preliminary clinical study. (2nd January 2019) - Wakisaka, Naohiro; Endo, Kazuhira; Kitazawa, Tomohiro; Shimode, Yuzo; Kato, Koroku; Moriyama-Kita, Makiko; Koda, Wataru; Ikeda, Hiroko; Ishikawa, Kazuya; Ueno, Takayoshi; Nakanishi, Yosuke; Kondo, Satoru; et al.
Abstract: Background: In sentinel lymph node (SLN) biopsy for head and neck cancers, the radioisotope method has been the gold standard. However, this method has several problems, such as unavoidable radiation exposure and requirements of expensive equipment. Aims/Objectives: To overcome these problems, we evaluated the contrast-enhanced ultrasonography (CEUS)-guided SLN-detection method, and predicted the SLN metastatic status using novel ultrasound technology, superb microvascular imaging (SMI). Methods: Ten patients (6 with oral and 4 with oropharyngeal cancers) without neck lymph node metastasis were enrolled in this study. Ultrasound contrast agent, Sonazoid ™, was infiltrated into the mucosa at the primary site to observe the lymphatic ducts and SLNs in the neck field. The detected SLNs were examined for blood flow using SMI to categorize the SLNs metastases-positive or negative. Results: SLNs were successfully detected in 8 out of 10 cases. In 7 out of the 8 cases, in whom SLNs were successfully detected, the metastatic status of SLNs was correctly diagnosed with SMI. Conclusions and significance: Although more clinical data are needed based on a larger cohort, establishing the CEUS-guided SLN-detection and criteria for the accurate diagnosis of SLN-metastases using SMI would be valuable as an alternative to radioisotope method, in oral and oropharyngeal cancers.